2005
DOI: 10.1016/j.devcel.2005.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Wnt11 Functions in Gastrulation by Controlling Cell Cohesion through Rab5c and E-Cadherin

Abstract: Wnt11 plays a central role in tissue morphogenesis during vertebrate gastrulation, but the molecular and cellular mechanisms by which Wnt11 exerts its effects remain poorly understood. Here, we show that Wnt11 functions during zebrafish gastrulation by regulating the cohesion of mesodermal and endodermal (mesendodermal) progenitor cells. Importantly, we demonstrate that Wnt11 activity in this process is mediated by the GTPase Rab5, a key regulator of early endocytosis, as blocking Rab5c activity in wild-type e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
236
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(266 citation statements)
references
References 38 publications
25
236
1
2
Order By: Relevance
“…Wnt11 regulates the E-cadherin-mediated cohesion of the mesoendoderm progenitors (9). In this process, Rab5, one of the key regulators of early endocytosis and intracellular trafficking, mediates Wnt11 activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt11 regulates the E-cadherin-mediated cohesion of the mesoendoderm progenitors (9). In this process, Rab5, one of the key regulators of early endocytosis and intracellular trafficking, mediates Wnt11 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt11, which acts in the noncanonical Wnt cascade, is involved in this process, controlling the cohesion of mesoendodermal cells through the Rab5c-mediated endocytosis of E-cadherin (9).…”
mentioning
confidence: 99%
“…It was recently reported that Wnt7a overexpression in the neural tube results in defective adherens junctions, with subsequent abnormalities in spinal neurulation (Shariatmadari et al, 2005). During zebrafish gastrulation, Wnt11 is required to modulate the cell surface localization of E-cadherin via a pathway involving the small GTPase Rab5, which regulates endocytosis (Ulrich et al, 2005). Signaling by another important growth factor TGF␤ 1 , leads to removal of E-cadherin from cell contacts, presumably by affecting the phosphorylation status of ␤-catenin (Vogelmann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…All confocal images were analysed and quantifi ed using ImageJ v. 1.45 ( http://rsb.info.nih.gov/ij / ). Th e membrane-to-cytosol ratio of respective experiments was calculated on single Z-planes using the methods developed by Janetopoulos et al 39 and Ulrich et al 40 For each of MEFs, 50 staining cells were used for quantitative analysis and statistical analysis ( Fig. 4d ).…”
Section: Methodsmentioning
confidence: 99%